HUBUNGAN PERILAKU IBU DALAM MEMBERSIHKAN BOTOL SUSU DENGAN KEJADIAN DIARE PADA BAYI DI DESA SALE KECAMATAN PLAOSAN KABUPATEN MAGETAN - Rahayu Setyaningsih; Lia Fitriyanti (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background. Cause of diarrhea one of them is the use of feeding bottles are not clean that facilitate contamination by germs such as Esherichia coli. When inserted into the bottle of milk that is not clean, there will be contamination of germs and bacteria if not immediately taken to grow. Sale village consists of 86 families with a number of children to 58 children aged 1 to 4 years, 31 of them are users of milk bottles. A survey from March to November 2014 data obtained 30% of the existing number of infants with diarrhea.Research purposes. To determine the corelation of maternal behavior in cleaning milk bottles with the incidence of diarrhea in the village of Sale District of Plaosan Magetan.Methods. The research design correlation with the approach of cross sectional method. Subjects were 31 mothers who have children with saturated sampling technique in which the entire population is used as a sample. Data obtained by questionnaire to determine the behavior of the mother in cleaning the bottles and the incidence of diarrhea in infants. The data obtained and analyzed by chi-square test with p = 0.05.Results. shows the behavior of the mother in cleaning milk bottle with both categories as many as 11 people (35.48%) and bad category 20 (64.52%) whereas the incidence of diarrhea result children who often experience diarrhea as many as 16 children (51.61% ) and rarely experience diarrhea as many as 15 infants (48.39%). Results of analysis using the chi-square test p 0.04 was obtained so that the value of p <0.05, which means that Ho is rejected and Ha accepted.The conclusion from this study is that there are corelation mother's behavior in cleaning milk bottles with the incidence of diarrhea in the village of Sale District of Plaosan Magetan.Â Keywords: Behavior, Milk Bottle Hygiene, incidence of diarrhea.